Principles and Techniques in Handling Brachytherapy - A Short Review - Mohd Khairi, Nur Fatimah Zahra; Roszaini, Nurul Farhana; Othman, Siti Amira (Journal of Advanced Industrial Technology and Application, 2023)
Brachytherapy is a type of radiation that involves precisely placing radioactive sources directly into or close to the tumour. This treatment is recommended for people suffering from many forms of cancer. It is an ideal tool for delivering extremely high dosages to the tumour while limiting the risk of normal tissue consequences. Physicians from a variety of disciplines may be involved in either referring to or placing brachytherapy. Brachytherapy is required for many patients as either a main treatment or as part of their oncologic care. Brachytherapy can be used to treat a wide range of tumour locations, including gynaecological, urologic, rectal, cutaneous, and breast malignancies. In most brachytherapy treatments, a radiation oncologist, called a radiation oncologist, relies on imaging techniques such as CT scans and ultrasound during the planning and delivery of brachytherapy to accurately identify encapsulated materials. Let it be placed. By using implants, it is possible to deliver a higher radiation dose to a limited area than conventional external beam radiotherapy. This may be more effective at destroying cancer cells while causing minimal damage to surrounding normal tissue is placed in patients are sedated for all these procedures.